PUBLIC PUNISHMENT AND SELF-DEFENSE MECHANISM ON CANING IN ACEH - zulfikar zulfikar; M. Nur An Anshari (State of Islamic Institute Langsa, 2021)
This article examines public caning in Aceh using a psychological perspective. In 2018, the issue of the pros and cons of the implementation of public caning in Aceh did not have much attention. Suddenly, the new pros and cons emerged about the venue of caning which was initially held in public (courtyard) and then was held in a prison. The pros and cons emerged when the Government of Aceh did not plan to demonstrate public caning in order to protect the dignity of a convict. Using literature sources, this article sees that a psychological perspective can be taken into account in punishment policies in Aceh. The main argument in this article is that public punishment has a long-lasting psychological impact. This finding strengthens the opinion that there are differences in the objectives of the law applied by the Aceh government with the law implemented conventionally in Indonesia.